2009
DOI: 10.1111/j.1540-8167.2008.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Bipolar Left Ventricular Pacing Stimulus Intensity to Cardiac Depolarization and Repolarization in Humans with Cardiac Resynchronization Devices

Abstract: Increased LV stimulus intensity, independent of RV anodal capture, is associated with faster transventricular conduction time, changes in myocardial depolarization, and longer QT intervals. These findings have important implications on the relationship of programmed LV pacing output to pacing-induced proarrhythmia and clinical CRT response rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
0
21
1
Order By: Relevance
“…Increased stimulus intensity led to a prolongation of QTc from 539 ± 45 (0.5 V > LV threshold) to 559 ± 46 mseconds (5 V < LV threshold). These findings had important implications on the relationship of programmed LV pacing output to pacing‐induced proarrhythmia . Furthermore, high epicardial pacing output might induce the bigger delta VT‐CL and delta QRS duration during VT.…”
Section: Discussionmentioning
confidence: 99%
“…Increased stimulus intensity led to a prolongation of QTc from 539 ± 45 (0.5 V > LV threshold) to 559 ± 46 mseconds (5 V < LV threshold). These findings had important implications on the relationship of programmed LV pacing output to pacing‐induced proarrhythmia . Furthermore, high epicardial pacing output might induce the bigger delta VT‐CL and delta QRS duration during VT.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, although previous study suggested that programmed V-V delay had impact on QT, JT and Tp-e (16), it was different or not provided in our included studies. Thirdly, the intensity of pacing during our included studies was not available, although LV pacing intensity was proved to have a positive correlation with QT interval (38). Fourthly, although 14 studies were included in this meta-analysis, only 1 study provided all the four endpoints, more than half of the studies provided only 1 endpoint.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In this case, the wave front originates from the "virtual cathodes." Understanding anodal stimulation is important, because it may be advantageous to stimulate with an anode in certain situations [21][22][23][24].…”
Section: Unipolar Stimulationmentioning
confidence: 99%